Transport and firm areas : the African strategies of Bolloré’s Group - (:unkn) unknown (My University, 2001)
To identify Bolloré’s Group strategies enables us to take part in the actual debate about the impact of privatisation in Africa. The emergence of an African Bolloré’s area, centered upon transport and logistical activities, reveals a totally planned, effective logic of a private network. The spatial impacts of these monopolistic dynamics are showing contradictory consequences. If on one hand, private transport networks do contribute to a real modernisation of the African circulation space, on the other hand it may be reduced to small private enclave, slightly connected to outer territories. This contradiction will have to lead prospective looking at further planning operations and political frameworks.
Keywords: African Research